PEMBERDAYAAN EKONOMI KREATIF GUNA PENINGKATAN KESEJATERAAN MASYARAKAT KOTA BANJARMASIN - Rian Saputra; Sepreika Mutiyara (AN NUQUD, 2023)
The development of a creative economy can increase the income of a business in an area, especially in the South Kalimantan region in the city of Banjarmasin, in the village of Sungai Jinggah there is a location for a creative economy area where business people build their business in the fashion sector in the form of cloth or typical sasirangan clothes from the city of Banjarmasin which symbolizes custom and Culture in an area is one of the creative economic activities, especially the craftsmen who make sasirangan cloth. The sasirangan production house is capable of producing 50 to 300 pieces of sasirangan cloth in a day at a price of IDR 250,000 per sheet depending on the type of cloth. Sasirangan cloth comes from the word sirang which means a cloth tie or bond with various kinds of motifs. Why is the name called a dyed or dyed cloth, because the way the cloth is made is by tying it and then coloring it according to the desired motif and dipping it in water of the color you choose. The white cloth will be tied according to the desired pattern or motif or has been determined by the craftsman.